Revisions of the clavipes and pruni species groups of the genus Merodon Meigen, 1803 (Diptera, Syrphidae) - Ante Vujić; Snežana Radenković; Laura Likov; Nataša Kočiš Tubić; Grigory Popov; Ebrahim Gilasian; Mihajla Djan; Marina Janković Milosavljević; Jelena Ačanski (ZooKeys, 2024)
This study focuses on the avidus–nigritarsis lineage within the genus Merodon, exploring morphological, genetic, and distributional aspects of two related assemblies within this lineage: the clavipes and pruni species groups. An integrative taxonomic approach was followed to ensure comprehensive species identification and validation, using adult morphology, wing geometric morphometrics, and genetic analysis of the mtDNA COI gene. In the clavipes group, seven species were identified, including three new species: M. aenigmaticus Vujić, Radenković & Likov, sp. nov., M. latens Vujić, Radenković & Likov, sp. nov., and M. rufofemoris Vujić, Radenković & Likov, sp. nov. In the pruni group, our revision revealed a new species, M. aequalis Vujić, Radenković & Likov, sp. nov., and the revalidation of Merodon obscurus Gil Collado, 1929, stat. rev. Merodon pallidus Macquart, 1842 is redescribed. Diagnoses, identification keys to species, and distribution maps are provided, and neotypes for Syrphus clavipes Fabricius, 1781 and Merodon quadrinotatus (Sack, 1931) are designated. Additionally, the following new synonyms are proposed: M. clavipes albus syn. nov., M. clavipes ater syn. nov., M. clavipes niger syn. nov., and M. splendens syn. nov. are junior synonyms of M. clavipes; and M. velox armeniacus syn. nov. and M. velox anathema syn. nov. are junior synonyms of M. velox.